THE POLITICAL AND LEGAL DIMENSION OF INTER-CIVILIZATIONAL CHALLENGES OF THE GLOBALIZED WORLD - Ordenov, Serhii (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2023)
Introduction. In today's globalized society, the problems of inter-civilizational relations tend to intensify, because one of the manifestations of globalization is the uneven economic and socio-cultural development of different peoples, regions, civilizations, etc. The aim is to study the political-legal dimension of inter-civilizational challenges of the globalized world from socio-philosophical positions. Research methodology. The research uses cultural-civilizational and dialectical methods in their integrative combination. Axiological and historical approaches were also used, which contributed to a deeper understanding of the political and legal dimensions of the inter-civilizational challenges of the globalized world. Research results. It is emphasized that the positions of Western researchers of civilizational development reflect the self-awareness of the superiority of Western European society. This entails inconsistencies in the correlation of the terms "civilization" and "globalization" and the ambiguity of the term "civilization" itself: on the one hand, it presupposes certain universalist principles of development, and on the other hand, it clearly contains orientalism, thus calling into question the existence of non-Western forms of civilization. Discussion. In this way, one of the tools of globalization is hyperdiffusionism, which is based on the principle that one civilization, race, or one people, due to its peculiarities, are the creators of all the benefits that less developed civilizations and peoples borrowed from them. Therefore, non-Western peoples resist not the principles of the rule of law, but the rules and standards established by the Western world to artificially manage globalization development and exert influence on social consciousness. Conclusions. This largely determines the political and legal dimension of the inter-civilizational challenges of the globalized world, due to which the conflict of civilizations can be considered as an inevitable consequence of globalization.